Anticipation in sport: Fifty years on, what have we learned and what research still needs to be undertaken?. (May 2019) - Williams, A.M.; Jackson, R.C.
Abstract: The ability to anticipate what will happen next is critical to performance in many sports as well as other professional domains. We review progress made in our scientific understanding of this topic since the seminal work conducted some 50 years ago. We highlight advances in methods and measures and identify the different perceptual-cognitive skills that have been identified by researchers as playing a pivotal role in anticipation. We examine how these perceptual-cognitive skills are used in a dynamic and interactive manner to facilitate anticipation, as well as how their importance varies due to the stress placed upon athletes by anxiety and fatigue. We summarise the impact of existing research on the development of training programs that facilitate skill acquisition. Finally, we provide some suggestions for future research in this area. We encourage continued growth in recent research exploring the role of contextual information in anticipation and present suggestions as to how the translational impact of this work can be increased in applied domains. Highlights: Anticipation underpinned by several interacting perceptual-cognitive skills. These include the use of postural cues, pattern recognition and the available contextual information. Experts pick up key sources of information by better integrating peripheral and foveal vision. Anticipation is supported by the ability to detect deceptive intent. Anticipation skill may be trained successfully through a variety of perceptual training protocols.